KEPERCAYAAN MEMEDIASI PENGARUH NILAI PELANGGAN, GREEN MARKETING, SOCIAL MEDIA MARKETING DENGAN KEPUTUSAN PEMBELIAN (Studi Pada Pelanggan Herbalife Di Kota Banjarmasin) - Rezqy Amalia; Tinik Sugiati; Ikhwan Faisal (JWM (JURNAL WAWASAN MANAJEMEN), 2021)
This research aims to find out and analyze 1) the influence of customer value on purchasing decisions, 2) the influence of green marketing on purchasing decisions, 3) the influence of social media marketing on purchasing decisions, 4) the influence of trust on purchasing decisions, 5) the effect of trust mediation in the relationship between customer value and purchasing decisions, 6) the effect of trust mediation in the relationship between green marketing and purchasing decisions, 7) the effect of trust mediation in the relationship between social media marketing and purchasing decisions. The Sampling method of this study is purposive sampling. The sample size amounted to 115 samples distributed to herbalife customer respondents in Banjarmasin (South Kalimantan). The data analysis used is SEM analysis (Structural Equation Model) using Partial Least Square (PLS) analysis technique. The results of this study proved that 1) customer value has significant influence on purchasing decisions; 2) green marketing has not significant influence on purchasing decisions; 3) social media marketing has significant influence on purchasing decisions; 4) trust has significant influence on purchasing decisions; 5) trust has the effect of mediation in the relationship between customer value and purchasing decisions; 6) trust has no effect mediation in the relationship between green marketing and purchasing decisions; 7) trust has no effect mediation in the relationship between social media marketing and purchasing decisions